KAJIAN KARAKTER KAWASAN DALEM PANGERAN DI YOGYAKARTA SEBAGAI ARAHAN PENATAAN DAN PENGEMBANGAN KAWASAN - , EKA WIDYANINGSIH ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Yogyakarta in its development can not be separated from the presence of Kraton (Palace), Alun-alun (Square), Masjid Besar (Great Mosque), the Dutch buildings and commercial buildings. But other than that, the presence of Dalem Pangeran (Nobleâs Residence) also has roles to the development of Yogyakarta. Nobleâs Residence region is one of the region whose development is very rapid in Yogyakarta. Nobleâs Residence is âurban heritageâ region which in this region has different characters with other regions. Nobleâs Residence characters can be seen from its physical and non- physical elements. This study is preceded by searching the characters of Nobleâs Residence. The character of Dalem Pangeran is identified based on its changes of morphology, typology and function. Based on changes in fields, it will get the character-forming elements that can contribute to the development of Jogjakarta.